Multi-Drug Resistant Chronic Myeloid Leukemia: Report of Two Cases and Review of Literature (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: In the last one decade first generation tyrosine kinase inhibitor (TKI), imatinib mesylate was the choice of treatment in Chronic Myeloid Leukemia (CML) but recently, a considerable number of patients have developed resistance to first as well as second generation TKIs.Objective: To present two cases which were first and second generation TKIs resistant and to review multidrug resistant CML.Materials and Methods: Relevant articles and literatures were retrieved from different journals and web pages to find out the mechanism of development of drug resistance in chronic myeloid leukaemia.Discussion: Two cases of drug resistant CML were found in Combined Military Hospital (CMH), Dhaka cantonment. Extensive review of the literature showed that two mechanisms, namely Breakpoint Cluster Region-Abelson (BCR-ABL) dependent and independent mechanisms, are mainly responsible for multi drug resistant (MDR) CML. In Bangladesh, it is difficult to identify the exact mechanism of development of drug resistance in CML. In a few cases, sample from CML patients are sent overseas to detect any new mutation in TKI binding domain of BCR – ABL fusion gene but it is not possible to find out other mechanisms responsible for drug resistance in CML.Conclusion: To overcome the drug resistance in CML, it is important to use the conventional drugs used in the treatment of CML meticulously and regularly as irregular use and discontinuation of treatment will permit the development of drug resistance.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 135-140